THE EFFECT OF BANK-SPECIFIC FACTORS ON ISLAMIC BANKS’ STABILITY - Alam, Md. Mahbub; Yusoff , Wan Sallha; Muhd Yusuf, Dayang Hasliza; Abdul Ghani, Mohd Rosli; Jamaluddin, Raziff; Kamaruddin, Nur Syuhadah; Ahsan, Arif (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The inconsistency in Islamic banking stability in Bangladesh is due to several challenges, including bank-specific factors. This study investigates the impact of bank-specific factors on the stability of Islamic banks in Bangladesh from 2012 to 2023. By analyzing key financial ratios and indicators, the research identifies critical determinants of stability in the context of Islamic banking. The study employs a panel dataset from seven Islamic banks, utilizing Feasible Generalized Least Squares (FGLS) to address cross-sectional dependence and heteroscedasticity. Key findings reveal that asset quality is the most significant factor influencing bank stability, highlighting the importance of maintaining a strong loan portfolio. Income diversification also plays a crucial role in mitigating risks by reducing reliance on a single source of income. Conversely, poor managerial efficiency and liquidity risk were found to have a negative impact on stability. While capital adequacy is typically associated with stability, the study suggests that excessively high capital reserves may lead to inefficiencies, reducing overall stability. Interestingly, the study finds that Sharia-compliant contracts (ISCON) do not significantly impact stability. These findings reaffirm the multi-dimensional character of bank stability, with efficient management, superior asset quality, diversification of income structure, and wise liquidity strategy being key. The study has identified valuable areas that can enhance the resilience of Islamic banks, focusing on specific areas that will yield future regulatory and operational benefits in the industry.